A rapid route for the preparation of pyrimido[5, 4-d]- and pyrido[3, 2-d]oxazoles. Issue 19 (6th May 2015) - Lemaire, Lucas; Leleu-Chavain, Natascha; Tourteau, Aurélien; Abdul-Sada, Alaa; Spencer, John; Millet, Régis
Graphical abstract: Abstract: Starting from a 5-amino-2-phenyloxazole-4-carbonitrile building block3, obtained by reaction of benzoyl chloride (1 ) and aminomalononitrile p -toluenesulfonate (2 ), a large range of molecules were synthesized in one or two steps. A total of seven pyrimido[5, 4- d ]oxazoles5 (a –d )–8 and four pyrido[3, 2- d ]oxazoles9 –12 have been synthesized. Moreover, synthetic procedures have been adapted to overcome the instability of the oxazole ring.